Effects of preseason training on the sleep characteristics of professional rugby league players - Thornton, H. R.; Delaney, J. A.; Duthie, G. M.; Dascombe, B. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate the influence of daily and exponentially weighted moving training loads on subsequent nighttime sleep. Methods: Sleep of 14 professional rugby league athletes competing in the National Rugby League was recorded using wristwatch actigraphy. Physical demands were quantified using GPS technology, including total distance, high-speed distance, acceleration/deceleration load (SumAccDec; AU), and session rating of perceived exertion (AU). Linear mixed models determined effects of acute (daily) and subacute (3- and 7-d) exponentially weighted moving averages (EWMA) on sleep. Results: Higher daily SumAccDec was associated with increased sleep efficiency (effect-size correlation; ES=0.15; ±0.09) and sleep duration (ES=0.12; ±0.09). Greater 3-d EWMA SumAccDec was associated with increased sleep efficiency (ES=0.14; ±0.09) and an earlier bedtime (ES=0.14; ±0.09). An increase in 7-d EWMA SumAccDec was associated with heightened sleep efficiency (ES=0.15; ±0.09) and earlier bedtimes (ES=0.15; ±0.09). Conclusions: The direction of the associations between training loads and sleep varied, but the strongest relationships showed that higher training loads increased various measures of sleep. Practitioners should be aware of the increased requirement for sleep during intensified training periods, using this information in the planning and implementation of training and individualized recovery modalities.